ECONOMIC ASPECTS AND CHALLENGES IN PRECISION AGRICULTURE - N. Penev; M. Petrov (Trakia Journal of Sciences)
Precise agriculture is an intersection in which meet high technologies, knowledge of the earth, soil, climate and good practices in agricultural activity. Economic aspects with precise agriculture are related to the introduction of those practices that can help improving the optimization of costs and achievement of higher quality products and better crop collection rates. In order to introduce the practices and techniques of precise agriculture specific investments are required in: information assurance, agro -technical procedures, monitoring services, and the use of GPS devices for mapping the field and planning the production process according to the specific needs of the farm. There are a wide variety of techniques that could be introduced in the production process, but only in certain cases these practices could be viable and could lead to real pay-back in a reasonable period of time and of course, could lead agricultural production to optimization levels , reducing costs of exploitation and improving financial statements of the farm.